Kajian Literatur: Pendekatan Pembelajaran, Disiplin, dan Pengembangan Karakter pada SD di Jepang dan Indonesia: Penelitian - Hendriyadi, Hendriyadi; Widuri, Ratih; Murba, Amelia; Madri, Madri; Subekti, Woro; Hudaidah, Hudaidah; Gulo, Fakhili; Safitri, Erna Retna (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze learning approaches, disciplinary culture, and character development strategies in elementary education in Japan and Indonesia through a comprehensive literature review. Using a literature review research design, data were obtained from national and international journals, academic books, educational organization reports, and relevant previous research findings from the past ten years. The findings indicate that Japan has successfully implemented active, collaborative, and contextual learning integrated with school routines, thereby shaping students' character through direct experience. In contrast, Indonesia, which has adopted a competency-based curriculum, still faces challenges such as pedagogical consistency, disparities in teacher quality, and a weak school culture that supports active learning and character education. In terms of discipline, Japan implements an approach based on collective responsibility and self-regulated behavior, while Indonesia is still in the transition process towards positive discipline that focuses on strengthening social-emotional competencies. Gap analysis reveals differences in the integration of learning, character, and school culture that impact the effectiveness of elementary education in both countries. This study presents a novelty in the form of mapping the state of the art that shows the relationship between learning approaches and character development in an international comparative context.